2008
DOI: 10.1111/j.1600-051x.2008.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental gingivitis: reproducibility of plaque accumulation and gingival inflammation parameters in selected populations during a repeat trial

Abstract: These results indicate that our experimental gingivitis model is reproducible to some extent in selected populations. The high reproducibility of plaque and, to a lesser extent, of inflammation parameters under the employed controlled conditions could be a valuable tool in gingivitis research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 21 publications
4
31
0
1
Order By: Relevance
“…As shown by our data, our participants displayed almost absolute periodontal health at baseline, reflected by an average GI at the experimental sites of 0.1, reached a mean GI of 1.6 and 1.8 at 21 days in the induction and resolution groups, respectively, and returned to an average GI of 0.7 two weeks after prophylaxis. Although these are obviously crude comparisons, based on averages of categorical indices, it is notable that 6 of the 20 participants in our study did not develop gingival inflammation beyond a GI score of 1 at day 21, consistent with the earlier documented heterogeneity in the clinical inflammatory response during experimental gingivitis (Tatakis and Trombelli, 2004, Trombelli et al, 2008), possibly reflecting lack of full compliance as well. Second, a more important difference between the two studies from a design perspective is the number of gingival tissue samples harvested from each participant and the time interval between the consecutive biopsies.…”
Section: Discussionsupporting
confidence: 89%
“…As shown by our data, our participants displayed almost absolute periodontal health at baseline, reflected by an average GI at the experimental sites of 0.1, reached a mean GI of 1.6 and 1.8 at 21 days in the induction and resolution groups, respectively, and returned to an average GI of 0.7 two weeks after prophylaxis. Although these are obviously crude comparisons, based on averages of categorical indices, it is notable that 6 of the 20 participants in our study did not develop gingival inflammation beyond a GI score of 1 at day 21, consistent with the earlier documented heterogeneity in the clinical inflammatory response during experimental gingivitis (Tatakis and Trombelli, 2004, Trombelli et al, 2008), possibly reflecting lack of full compliance as well. Second, a more important difference between the two studies from a design perspective is the number of gingival tissue samples harvested from each participant and the time interval between the consecutive biopsies.…”
Section: Discussionsupporting
confidence: 89%
“…at completion of a 21-day experimental gingivitis trial). In this respect, we found that subjects who had showed a consistently higher and lower severity of plaque-induced gingival inflammation following two consequent experimental gingivitis trials also showed a consistently higher and lower gingival inflammation when observed in their ''natural state'' (Trombelli et al 2008). Therefore, in the present study, we adopted our model to evaluate the IL-1b levels in GCF and serum in either N-O or experimentally induced (E-I) plaque-associated gingivitis.…”
mentioning
confidence: 81%
“…After a first randomized split-mouth localized experimental gingivitis clinical trial (first trial), conducted from October 2000 to November 2001, two sub-populations of periodontally healthy individuals were identified, respectively, defined as high responders (HR, n 5 24) and low responders (LR, n 5 24), and characterized by significantly different severity of gingivitis to similar amounts of plaque deposits (Trombelli et al 2004c). On January 2002, we recalled all HR and LR individuals to verify their availability and eligibility for a second trial (repeat trial) (Trombelli et al 2008). Volunteers underwent the repeat trial between April and November 2002.…”
Section: Experimental Design and Study Populationmentioning
confidence: 99%
“…Varying methods have been proposed to assess gingival bleeding. Among those, the most commonly used are: BOP score, scores of 2 to 3 of the gingival index and the angulated bleeding index (AngBS) . These methods are based on a different diagnostic maneuver with respect to probing stimulation of the gingival tissues.…”
Section: Methodsmentioning
confidence: 99%